2017
DOI: 10.1021/acs.jpca.7b05199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chromophoric Dissolved Organic Matter on Anthracene Photolysis Kinetics in Aqueous Solution and Ice

Abstract: We measured photolysis kinetics of the PAH anthracene in aqueous solution, in bulk ice, and at ice surfaces in the presence and absence of chromophoric dissolved organic matter (CDOM). Self-association, which occurs readily at ice surfaces, may be responsible for the faster anthracene photolysis observed there. Photolysis rate constants in liquid water increased under conditions where anthracene self-association was observed. Concomitantly, kinetics changed from first-order to second-order, indicating that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
3
11
2
Order By: Relevance
“…Table 1 shows first order anthracene photodegradation rate constants in aqueous solution and artificial snow. In agreement with several previous studies, 13,17,36,37 though in contrast to Ref. 10, we measure a larger rate constant in the frozen sample.…”
Section: Photodegradation Kineticssupporting
confidence: 93%
See 3 more Smart Citations
“…Table 1 shows first order anthracene photodegradation rate constants in aqueous solution and artificial snow. In agreement with several previous studies, 13,17,36,37 though in contrast to Ref. 10, we measure a larger rate constant in the frozen sample.…”
Section: Photodegradation Kineticssupporting
confidence: 93%
“…33 If all anthracene molecules at the surface of frozen NaCl solutions are in the brine channels, we calculate anthracene concentrations on the order of -20 µM at deposition times corresponding to 50 -200% of a formal monolayer, based on a liquid volume fraction of 15% for 0.6 M NaCl solutions at −15 o C. 22 This is well above anthracene's saturation limit in room temperature DI water (~0.2 µM); 34 we have shown that the 380 nm emission peak of anthracene becomes increasingly suppressed with increasing anthracene concentration at concentrations greater than ~10 µM. 17 High anthracene concentrations in brine channels, along with salting-out due to high NaCl concentrations in the brine channels (~4 M), 35 likely explain the excimer-like anthracene emission observed at the frozen salt solution surface.…”
Section: Spectra and Mapsmentioning
confidence: 68%
See 2 more Smart Citations
“…This indicates that the inner filter effect was negligible in our experiments. We recently reported that DOM does not greatly affect anthracene photodegradation kinetics in aqueous solution, even at concentrations much greater than those present in our Sargasso Sea water samples . The observed deviations in anthracene’s photodegradation kinetics in Sargasso Sea water from those in DI water are therefore likely primarily due to effects of halides and other heavy atoms.…”
Section: Results and Discussionmentioning
confidence: 41%